Review of Holocene wildfowl extinctions - Young, H Glyn; Tonge, Simon J; Hume, Julian P (Wildfowl, 1996)
Brief accounts are given of 54 wildfowl taxa (Anseriformes) known to have become extinct during the Holocene Period (the last 10,000 years). Distribution, probable taxonomic affinities, and the causes of decline of these, predominantly island-living birds are discussed.